Penggunaan Algoritma Backpropagation dalam penentuan Lokasi Objek menggunakan Kekuatan Sinyal Wifi - Hani Rubiani (Universitas Negeri Padang, 2019)
This research was conducted to estimate the location of objects in buildings which are fundamental challenges and indeed there have been many studies on localization in buildings based on signal strength by utilizing devices in it such as Wifi signals. The position of the object to receive signal strength calculated in this paper uses a classification algorithm called Artificial Neural Networks (ANN) or in English known as Artificial Neural Network (ANN) with a type of feed forward network or Backpropagation. The experiments conducted showed that the achievement of the accuracy value of the validation results based on the dataset was around 44.56%.